Keterampilan Proses Sains dalam Pembelajaran Sains: Kajian Literatur - Maryanto, Yudha Ikhwal; Selaras, Ganda Hijrah; Lufri, Lufri; Rahmi, Fitri Olvia (Lembaga Yasin AlSys, 2026)
Science process skills are a critical competency in biology education because they shape students’ ability to think and work scientifically, yet structured mapping of recent research findings on this topic remains limited. This study aimed to examine science process skills in biology learning based on findings from previous studies. A literature study method was employed by analyzing eight national and international research articles published between 2018 and 2024. The articles were retrieved from the Google Scholar, ScienceDirect, and ERIC databases and selected based on their relevance to science process skills in biology learning. Data were analyzed using content analysis by reviewing each article’s research objectives, learning context, indicators of science process skills, and main findings. The review shows that students’ science process skills tend to develop through biology learning that emphasizes scientific activities such as observation, problem formulation, experimentation, data analysis, and scientific communication, while valid and standardized assessment of science process skills plays an important role in supporting their development. Overall, this study provides a comprehensive overview of the role of science process skills as a foundation for biology learning oriented toward scientific processes and serves as a reference for further research in science education.